Exploring the antibacterial mechanisms of chemically characterized essential oils from leaves and buds of Syzygium aromaticum (L.) Merr. et Perry against Staphylococcus aureus and Pseudomonas aeruginosa - Al-Mijalli, Samiah Hamad; El Hachlafi, Naoufal; Abdallah, Emad M.; Jeddi, Mohamed; Assaggaf, Hamza; Qasem, Ahmed; Alnasser, Sulaiman Mohammed; Attar, Ammar; Naem, Mommen Adnan; Lee, Learn Han *; Bouyahya, Abdelhakim; Mrabti, Hanae Naceiri (Elsevier, 2023)
Syzygium aromaticum (L.) Merr. et Perry is a medicinal plant extensively used in international pharmacopeia to treat different ailments, including infectious diseases. In this study, we designed to determine the chemical constituents of S. aromaticum essential oils extracted from leaves (CEOL) and floral buds (CEOB) and their antibacterial mechanism of action against S. aureus and P. aeruginosa. The volatile components from CEOL and CEOB were detected using gas chromatography coupled to a mass spectrometer (GC/MS). The results indicated that eugenol was the major component for both CEOL (65.75%) and CEOB (74.03%). The antibacterial findings demonstrated the potent antibacterial activity of CEOL and CEOB. These oils exhibited significant zones of inhibition against all tested bacteria, including S. aureus ATCC 29213, K. aerogenes ATCC 13048, P. aeruginosa ATCC 27853, and E. coli ATCC 25922, surpassing the effects of antibiotics. Additionally, they displayed low minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs), indicating their bactericidal nature (MBC/MIC <4.0). Time-kill kinetics revealed that CEOB was more effective than CEOL at sub-MIC doses, eradicating S. aureus within 12 h and P. aeruginosa within 12–24 h. The cell membrane permeability test demonstrated that CEOL and CEOB treatment affected the relative conductivity of S. aureus and P. aeruginosa at both MIC and sub-MIC concentrations, indicating disruption of the bacterial membrane and influencing their growth and viability. Furthermore, the cell membrane integrity test showed that the addition of CEOL and CEOB to S. aureus and P. aeruginosa cultures led to significant protein release from the bacterial cells. The results of the anti-biofilm activity test confirmed the efficacy of S. aromaticum EOs, particularly CEOB, as potent anti-biofilm agents, suggesting its potential effect on inhibiting quorum sensing. Scanning electron microscope (SEM) microscopy further revealed significant alterations in bacterial cells treated with CEOB essential oil, including damage to the cell wall and distorted cell morphology, highlighting its impact on bacterial cell structure. Presented information suggests the use of clove EOs as natural alternatives for sustainable application in food and pharmaceutical industries.